Control de oxidación con ácido ascórbico y temperatura de almacenamiento en la determinación de la vida útil de salprieta - Cantos Loor, Aura Andrea (2013)
This research determined the oxidation control by ascorbic acid and storage temperature of salprieta life cycle. We used a completely randomized design (DCA) under AXB Bifactorial. There were three replicates for each treatment and used as experimental unit 2 kg of salprieta. For the experiment, the salprieta was packaged with different percentages of ascorbic acid (100ppm, 200ppm and 300ppm) at different temperatures (10°C, 20°C and 30°C). Using a sensory panel with unqualified judges established that the best treatment is a1 * b2, which corresponds to a rate of 200 ppm, and a temperature of 10°C, doing the humidity Chemical analyzes (INEN 464), fat (40 AC 17°th), protein (INEN 465), fiber (INEN 542), ash (INEN 467) parameters established by the specifications of the Colombian Institute of Family Welfare (ICFW), (2012) and life cycle according to product deterioration. In the treatment a1*b1 was observed the variation of Ascorbic acid (100ppm) during storage at 10°C, through the formulation of ln showing that has a stability of 46 days being the most useful.